Synthesis of Fluorinated Amphiphilic Block Copolymers Based on PEGMA, HEMA, and MMA via ATRP and CuAAC Click Chemistry - Erol, Fatime Eren; Sinirlioglu, Deniz; Cosgun, Sedat; Muftuoglu, Ali Ekrem (HINDAWI LTD, 2014)
Synthesis of fluorinated amphiphilic block copolymers via atom transfer radical polymerization (ATRP) and Cu(I) catalyzed Huisgen 1,3-dipolar cycloaddition (CuAAC) was demonstrated. First, a PEGMA and MMA based block copolymer carrying multiple side-chain acetylene moieties on the hydrophobic segment for postfunctionalization was carried out. This involves the synthesis of a series of P(HEMA-co-MMA) random copolymers to be employed as macroinitiators in the controlled synthesis of P(HEMA-co-MMA)-block-PPEGMA block copolymers by using ATRP, followed by a modification step on the hydroxyl side groups of HEMA via Steglich esterification to afford propargyl side-functional polymer, alkyne-P(HEMA-co-MMA)-block-PPEGMA. Finally, click coupling between side-chain acetylene functionalities and 2,3,4,5,6-pentafluorobenzyl azide yielded fluorinated amphiphilic block copolymers. The obtained polymers were structurally characterized by H-1-NMR, F-19-NMR, FT-IR, and GPC. Their thermal characterizations were performed using DSC and TGA.
Keywords: CONSTANT FLUOROPOLYMER FILMS; POLY(ETHYLENE GLYCOL); POLYMERIZATION; METHACRYLATE; COMBINATION; POLYSTYRENE; COATINGS; BEHAVIOR; COMPLEX; Polymer Science